Anoxygenic photosynthetic bacteria and Bacillus spp. as alternative bacterial diets to enhance lifespan and proximate composition in Moina macrocopa - Chewapat Saejung; Thararin Ngamsiri; Anuwat Chaiyarat (Aquaculture Reports, 2024)
The nutritive value of Moina macrocopa determines the quality of the aquatic larvae in aquaculture, and diets stimulating their productivity are essential. Herein, we have proposed alternative bacterial diets containing anoxygenic photosynthetic bacteria (Rhodopseudomonas faecalis PA2, Rhodopseudomonas palustris, and Rhodobacter sphaeroides) and Bacillus spp. (Bacillus subtilis and Bacillus licheniformis) for M. macrocopa culture. We compared the growth profile, nutritional productivity, and proximate composition of the bacteria in synthetic media and aquaculture water. All tested bacteria demonstrated growth and reproducibility in aquaculture water without nutrient supplementation. Cultivation of anoxygenic photosynthetic bacteria showed high nutritional productivity with cost-effectiveness, which were approximately four-fold lower than that of Bacillus spp. Bacillus spp. showed greater tolerance to high ammonia (5–160 mg/L) and nitrite (5–100 mg/L) concentrations than did anoxygenic photosynthetic bacteria, with B. licheniformis showing the highest growth rates. The effects of dietary administration of these bacteria on M. macrocopa’s lifespan and proximate composition were investigated. B. subtilis positively influenced the fecundity, reproduction, and protein content but reduced its average longevity, whereas treatment with R. palustris yielded 84.59 % crude protein but reduced the lifespan of M. macrocopa. R. faecalis PA2 dietary utilization had an overall positive effect on the net reproductivity and average longevity without consequences. The average initial reproductive age, number of broods per female, specific growth rate, and protein content were greater than those due to control diet (Chlorella vulgaris). Considering the lifespan and proximate composition of M. macrocopa, R. faecalis PA2 may be a novel diet for M. macrocopa and should be further investigated in other cladocerans.